The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.35790/ecl.3.1.2015.7402
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Penderita Stroke Iskemik Yang Di Rawat Inap Di Rsup Prof. Dr. R. D. Kandou Manado Tahun 2012-2013

Abstract: Stroke is rapidly developing clinical signs of focal or global disturbance of cerebral function, with symptoms lasting 24 hours or longer or leading to death, with no apparent cause other than of vascular origin. This study aimed to know characteristic of ischemic stroke patients hospitalized at Prof.Dr.R.D.Kandou hospital in 2012-2013. This research is descriptive retrospective research using secondary data, including the ischemic stroke patient’s medical record. The results showed the highest percentage isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 3 publications
1
6
0
5
Order By: Relevance
“…Hal ini sesuai dengan penelitian yang dilakukan di RSUP Prof. Dr. R. D. Kandou Manado tahun 2012-2013 bahwa jumlah pasien laki-laki (52%) lebih banyak dibanding perempuan. 12 Meski penelitian di Singapura didapatkan hasil bahwa jenis kelamin tidak berkorelasi secara signifikan dengan LOS 13 namun, hasil dari penelitian Sagrat Cor Hospital of Barcelona 14 menyatakan bahwa perempuan dan laki-laki memiliki perbedaan karakteristik faktor risiko, presentasi stroke, dan penyebab stroke yang dapat mempengaruhi LOS.…”
Section: Bahasanunclassified
“…Hal ini sesuai dengan penelitian yang dilakukan di RSUP Prof. Dr. R. D. Kandou Manado tahun 2012-2013 bahwa jumlah pasien laki-laki (52%) lebih banyak dibanding perempuan. 12 Meski penelitian di Singapura didapatkan hasil bahwa jenis kelamin tidak berkorelasi secara signifikan dengan LOS 13 namun, hasil dari penelitian Sagrat Cor Hospital of Barcelona 14 menyatakan bahwa perempuan dan laki-laki memiliki perbedaan karakteristik faktor risiko, presentasi stroke, dan penyebab stroke yang dapat mempengaruhi LOS.…”
Section: Bahasanunclassified
“…The results of this study are similar with a study conducted in Manado, which found that mild alcohol consumption is protective against stroke events. 31 In contrast, a meta-analysis in Australia reported that respondents who consumed alcohol ±200 ml-400 ml showed a low adjusted RR for a stroke while the ±1000 ml alcohol use showed a higher adjusted RR for stroke. 32 Another meta-analysis also reported that alcohol consumed >1000 ml is a risk factor for stroke in Asian populations.…”
Section: Discussionmentioning
confidence: 96%
“…Factors that can't be modified include mature enough and sex, while factors that can be changed fuse hypertension, diabetes mellitus, lipid profile, alcohol drunk and smoking. (Patricia, Kembuan and Tumboimbela, 2015) Hypertension a significant danger factor for stroke. Arranged as hypertension when pulse is more noteworthy than or equivalent to 140/90 mmHg.…”
Section: Discussionmentioning
confidence: 99%